2017
DOI: 10.1038/s41598-017-08197-2
|View full text |Cite
|
Sign up to set email alerts
|

Lacrimal Gland Repair after Short-term Obstruction of Excretory Duct in Rabbits

Abstract: Aqueous tear-deficient dry eye is a multifactorial chronic disorder in which the lacrimal glands fail to produce enough tears to maintain a healthy ocular surface. The existence of lacrimal gland stem/progenitor cells was proposed in several species, yet their origin and characteristics are not very clear. Here, we investigated the presence of resident progenitor cells and their regenerative potential in a rabbit model with lacrimal gland main excretory duct ligation-induced injury. The ligation-injured lacrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Nestin þ cells are also increased in a manner similar to that of the K14 þ cells. 25 Furthermore, EMTassociated markers in LG tissues were unregulated after ductal ligation-induced injury and ligature release, in a manner similar to that of an IL-1a injection model. Cells obtained from injured LGs could proliferate from a single cell and were passaged >12 times.…”
Section: For Review)mentioning
confidence: 78%
See 1 more Smart Citation
“…Nestin þ cells are also increased in a manner similar to that of the K14 þ cells. 25 Furthermore, EMTassociated markers in LG tissues were unregulated after ductal ligation-induced injury and ligature release, in a manner similar to that of an IL-1a injection model. Cells obtained from injured LGs could proliferate from a single cell and were passaged >12 times.…”
Section: For Review)mentioning
confidence: 78%
“…In the salivary gland, the ductal ligation model induced the proliferation of various cell types, including acinar, ductal, and myoepithelial cells, during tissue repair after ligature release. 23 Recently, two studies 24,25 have been reported regarding LG dysfunction in animal models (murine and rabbit) by ductal ligation. Both studies show that the ligation-injured LGs decrease in size and weight dramatically and exhibit impaired tear secretion with inflammatory cell infiltration.…”
Section: For Review)mentioning
confidence: 99%
“…Besides these three epithelial cell types, the lacrimal gland stroma also contains fibroblasts that secrete extracellular matrix, and mast cells that produce histamines and matrix proteins into the interstitial spaces. The regenerative ability of lacrimal gland tissue was reported by several groups 68. However, researchers still debate the roles of specific cellular components in regeneration.…”
Section: Introductionmentioning
confidence: 98%
“…Based on the etiology and classification of dry eye, different animal models have been developed over the years [4,5]. In rabbits, dry eye has been induced by many procedures such as dacryoadenectomy [6], female and male castration [7,8], desiccating stress [9], induced autoimmune dacryoadenitis [10], injection of the lacrimal gland with concanavalin A [11], injury of the drainage duct [12], nerve denervation [13], and topical instillation of atropine [14] or benzalkonium chloride (BAC) [15]. e current publication is focused on the topical instillation of BAC.…”
Section: Introductionmentioning
confidence: 99%